2015
DOI: 10.1002/clc.22443
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Evaluation of the Right Ventricle: An Updated Review

Abstract: The assessment of the volumes, function, and mechanics of the right ventricle (RV) is very challenging because of the anatomical complexity of the RV. Because RV structure, function, and deformation are very important predictors of cardiovascular morbidity and mortality in patients with heart failure, pulmonary hypertension, congenital heart disease, or arrhythmogenic RV cardiomyopathy, it is of great importance to use an appropriate imaging modality that will provide all necessary information. In everyday cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 54 publications
1
49
0
2
Order By: Relevance
“…Additionally, the authors have shown that RV GLS < −20% is the most sensitive and specific predictor of RV dysfunction . Investigations have revealed RV GLS as one of the most important predictors of cardiovascular and total morbidity and mortality in a large number of cardiovascular disorders . Figure represents the evaluation of RV longitudinal strain.…”
Section: Rv Mechanics—basics and Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the authors have shown that RV GLS < −20% is the most sensitive and specific predictor of RV dysfunction . Investigations have revealed RV GLS as one of the most important predictors of cardiovascular and total morbidity and mortality in a large number of cardiovascular disorders . Figure represents the evaluation of RV longitudinal strain.…”
Section: Rv Mechanics—basics and Applicationmentioning
confidence: 99%
“…The development of cardiovascular medicine, particularly the improvement of cardiac imaging techniques, has revealed that the RV has a vital role in global cardiac function, cardiovascular and total morbidity, and mortality. Not only in diseases that predominantly involve pulmonary circulation, such as pulmonary hypertension and congenital heart diseases, but also in conditions that primarily affect the left ventricle (LV), such as heart failure and mitral and aortic valve disease …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this method requires increased radiation exposure, it provides dynamic images throughout the cardiac cycle allowing for precise and reproducible quantification of RV volume and function. 39 While CMR is traditionally used more frequently for quantification of volumes and ejection fraction, CT can be used as an alternative modality when CMR is contraindicated or unavailable. 14 CT like CMR provides multiplanar imaging of the RV with excellent endocardial definition and high spatial resolution.…”
Section: Ctmentioning
confidence: 99%
“…The importance of right ventricular (RV) structure and function has been underestimated in comparison with left ventricular remodeling for a long time. However, studies have shown that its structure and function is very important in patients with congenital heart disease and pulmonary hypertension, but afterward, the important role of RV remodeling has been proved in the patients with heart failure, heart transplantation, cardiomyopathies, and valvular heart disease . The influence of aortic stenosis (AS) and particularly of AS severity on RV remodeling is still debatable, and the data are scarce .…”
Section: Introductionmentioning
confidence: 99%